The utilization of a novel Outpatient Appropriateness Fragility Score to predict inpatient stay following biportal lumbar endoscopic decompression - Thomas E. Olson, M.D.; Carlos Maturana, M.D.; Christopher D. Hamad, M.D.; Alex M. Upfill-Brown, M.D.; William L. Sheppard, M.D.; Don Young Park, M.D. (North American Spine Society Journal, 2025)
ABSTRACT: Background: Biportal endoscopic spine surgery offers advantages such as reduced postoperative pain and faster recovery, often enabling same-day discharge. However, the patient-specific factors influencing the need for inpatient admission remain unclear. This study evaluates variables contributing to overnight stays following biportal lumbar endoscopic decompression and proposes a predictive fragility score. Methods: A retrospective analysis of prospectively collected data was conducted on 84 consecutive patients undergoing one- or two-level lumbar endoscopic decompression at a single U.S. academic center. Patients with trauma, tumor, infection, or revision procedures were excluded. Cohorts were divided by discharge status: same-day discharge (outpatient) versus one or more night hospital stay (inpatient). A novel fragility score (4–21 points) incorporating age, body mass index (BMI), comorbidities, and procedure type was developed. Sarcopenia was assessed using the psoas muscle index (PMI), defined as the ratio of psoas to vertebral cross-sectional area on preoperative imaging. Cutoff values were analyzed via Youden’s J statistic and receiver operating characteristic analysis. Results: Same-day discharge patients were significantly younger (55.3 vs. 68.5 years; p=.0003) and had lower American Society of Anesthesiologists (2.0 vs. 2.7; p<.0001) and Charlson Comorbidity Index scores (1.6 vs. 3.5; p<.0001). No significant BMI difference was observed (p=.4341). Outpatients more frequently underwent discectomy; inpatients more commonly received ULBD and two-level decompression (p<.0001, p=.0014). A fragility score ≥11 predicted inpatient stay with an area under the curve (AUC) of 0.810, outperforming Modified 5-Item Frailty Index (AUC 0.640). PMI did not differ between groups (p=.6732), with AUCs of 0.417 overall, and 0.482 (males), 0.487 (females). Fragility score and PMI were weakly correlated (r=–0.130). Conclusions: The proposed Outpatient Appropriateness Fragility Score effectively predicts inpatient admission after biportal lumbar decompression. Factors such as age, comorbidities, and surgical extent are more predictive than BMI or sarcopenia. This tool may guide preoperative planning and optimize resource utilization.